1991
DOI: 10.1161/01.hyp.17.3.278
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of renal function by angiotensin during chronic adrenergic stimulation.

Abstract: The purpose of the present study was to determine the role of angiotensin II (Ang II) in mediating renal responses to chronic intrarenal norepinephrine infusion. Norepinephrine was continuously infused for 5 days into the renal artery of unilaterally nephrectomized dogs at progressively higher daily infusion rates: 0.05, 0.10, 0.20, 030, and 0.40 /tg/kg/min. In three additional groups of dogs, norepinephrine infusion was repeated during chronic intravenous captopril administration to fix plasma Ang II concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…This indicates that at high levels of adrenergic stimulation, the renal vasoconstrictor effects of Ang II were diminished relative to those of NE. Based on the pronounced increases in PRA achieved at the highest infusion rates of NE used in the present study and our previous measurements of PRA during intrarenal NE infusion, 6 -13 ' 32 it is unlikely that the diminished role of Ang II in mediating the renal vasoconstriction at more intense degrees of renal adrenergic stimulation was due to an inability to achieve additional increments in Ang II. Rather, the diminished effects of Ang II on RBF, relative to those of NE, may be due to the differential sensitivity of preglomerular and postglomerular vessels to these vasoconstrictors.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…This indicates that at high levels of adrenergic stimulation, the renal vasoconstrictor effects of Ang II were diminished relative to those of NE. Based on the pronounced increases in PRA achieved at the highest infusion rates of NE used in the present study and our previous measurements of PRA during intrarenal NE infusion, 6 -13 ' 32 it is unlikely that the diminished role of Ang II in mediating the renal vasoconstriction at more intense degrees of renal adrenergic stimulation was due to an inability to achieve additional increments in Ang II. Rather, the diminished effects of Ang II on RBF, relative to those of NE, may be due to the differential sensitivity of preglomerular and postglomerular vessels to these vasoconstrictors.…”
Section: Discussionsupporting
confidence: 55%
“…In an earlier study, we found that chronic intravenous infusion of Ang II at the same hypertensive rate as used in the present study (5 ng/kg per minute) prevented captoprilinduced deterioration of renal function during infusion of NE into the renal artery over a period of several days. 6 The current findings indicate that even normal levels of Ang II prevent enhanced renovascular responses to acute adrenergic stimulation when captopril is administered chronically. In the absence of Ang II replacement, how might chronic captopril administration predispose the kidneys to excessive renal vasoconstriction during acute intrarenal NE infusion?…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations